The first experience of allogeneic bone marrow transplantation in a patient with Mycosis Fungoides (clinical report) - I. A. Kuklin; M. M. Kokhan; O. G. Rimar; T. S. Konstantinova; I. V. Anisimova; M. K. Kuklina (Лечащий Врач)
Background. Mycosis Fungoides is a primary epidermotropic T-cell lymphoma of the skin, characterized by the proliferation of small and medium-sized T-lymphocytes with cerebriform nuclei. Despite modern achievements in laboratory diagnostics and immunochemotherapy of hemoblastoses, Mycosis Fungoides remains an urgent problem for doctors of various profiles. At the onset of the disease, difficulties often arise in clinical and morphological diagnosis, and in the later stages of the disease, active monitoring and individual selection of the optimal treatment method are required. The indication for allogeneic bone marrow transplantation in patients with Mycosis Fungoides is under the age of 60 years in the absence of effect from other types of therapy, as well as early progression into the later stages of the disease. Thanks to the application of a multidisciplinary approach to the management of a patient with Mycosis Fungoides, it has become possible to implement the most effective method of treating this disease.Results. The authors describe a case of diagnosis and successful co-treatment of a 46-year-old patient with Mycosis Fungoides who consulted a dermatovenerologist at the Ural Research Institute of Dermatovenereology and Immunopathology clinic with complaints of abdominal rashes accompanied by painful sensations and periodic itching. The diagnosis was verified by pathomorphological and immunohistochemical studies of the skin biopsy. In the Department of Hematology, Chemotherapy and Bone marrow Transplantation of the Sverdlovsk Regional Clinical Hospital No 1, the patient underwent 6 courses of combined polychemotherapy, and partial remission was achieved. Taking into account the onset of the disease at a young age, the aggressive course and the late stage of the disease, the consultation decided to perform an allogeneic hematopoietic stem cell transplant for the patient. In the post-transplant period, simultaneously with standard systemic immunosuppressive therapy with cyclosporine A and mycophenolate mofetil, topical glucocorticosteroids and a dermatocosmetic agent with anti-inflammatory, antipruritic and regenerating effects were prescribed to the patient as external agents. The presented clinical case introduces dermatovenerologists and hematologists to the experience of successful bone marrow allotransplantation in a patient with Mycosis Fungoides. Currently, the patient is under the supervision of a hematologist and a dermatovenerologist.